ANALISIS UMUR REKSADANA, EXPENSE RATIO DAN KINERJA REKSADANA SAHAM DI PERUSAHAAN MANDIRI INVESTASI PERIODE 2014-2019 - Muhammad Helmi; Jumali Jumali (P3M STIE Mulia Darma Pratama, 2021)
Mutual funds are investment facilities that are used to raise funds from the investor community for further investment in securities portfolios by investment managers, and subsequently invested in stocks, bonds, time deposits, money market, and so on. Mutual fund performance is influenced by the determining factors of whether a mutual fund performs well or poorly, the mutual fund performance factor, namely the first is the age / age of the mutual fund (Fund Age), the second is the comparison between operating costs in one year and the average net asset value in one year (Expense Ratio) and the third is Net Asset Value (NAV). The formulation of the problems in this research are (1) How is the development of the age of equity funds in Mandiri Investasi for the 2014-2019 period? (2) How is the development of the stock mutual fund expense ratio at the Mandiri Investasi period of 2014-2019? net assets (NAV) of equity mutual funds performance at Mandiri Investasi for the 2014-2019 period. This study aims to determine the development of mutual funds age, expense ratio and net asset value (NAV) of the performance of Mandiri Investa Attractive (MITRA) equity funds in Mandiri Investasi for the period 2014-2019. The objects examined in this study are variables in the form of mutual funds age, expense ratio, and mutual fund performance (NAV). Methods of data analysis in this study using descriptive analysis methods. The results of the research conducted were the age development of Mandiri Investa Attraktf (MITRA) equity funds at the Mandiri Investasi company, which experienced an increase in age in 2014-2019. Expense ratio development in 2014-2019 has decreased. And in the development of equity mutual funds performance, namely the net asset value (NAV) in 2014-2019 experienced fluctuations.